Hash function of finalist SHA-3: analysis study - Alshaikhli, Imad Fakhri Taha; Alahmad, Mohammad A.; Munthir, Khansaa (Helvetic Editions LTD, Switzerland, 2013)
The National Institute of Standard and Technology (NIST) has suggested different principles for hash functions to avoid the blunders and to choice the ideal quality of hash function, which to be a measurement for the future of hash function generations. Therefore, the goal of the NIST contenders in SHA-3 between the hash functions is to be chosen as the winner in the end of 2012, and the beginning of 2013. Thus, for this reason the paper addresses the comparative and analysis study of the finalist SHA-3 candidates in: complexity of security, design and structure, as well as performance and cost, to measure the robustness of the algorithms in this area, through the Fundamentals Security Measurement Factors of Hash Function (FSMFHF) of Secure Hash Algorithm (SHA). Therefore, main idea from this comparison and analysis study between the finalist of SHA-3 candidates such as (BLAKE, Grostl, JH, Keccak, and Skein) is to investigate the tight security in the suitable designs of lightweight such as JH and Keccak for the future security of hash function. Moreover, they are investigating the high trade-off in (speed/memory) that implemented in Virtex-7 2000T of FPGAs family hardware. Whereas, excluded the rest of hash functions in this finalist, which are not investigated all the measurements of hash function as mentioned above.